Hiawatha's kind heart - Walt Disney (Winter Park, FL Advance Publishers, Inc., 1986)
Hiawatha treks through the wilderness
D., 11/12/05, R Madore
Keywords: Hiawatha; Forest animals; Friendship; Indians